2010
DOI: 10.3802/jgo.2010.21.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis to the ovaries from transitional cell carcinoma of the bladder and renal pelvis: a report of two cases

Abstract: Ovarian metastases from a primary urinary tract carcinoma are extremely rare. This can be difficult to distinguish from transitional cell carcinomas (TCC) of ovarian origin because of histologic similarity. A 65-year-old woman who was diagnosed with renal pelvis TCC 4 months prior was referred for evaluation of a left ovarian mass. A 47-year-old woman who underwent radical cystectomy due to bladder TCC 1 year ago was referred because of a right ovarian mass. Both patients underwent a bilateral salpingo-oophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The presence of a component of benign or borderline Brenner tumor confirms an ovarian primary tumor. TCC of the ovaries has mucin pools and thick papillae with smooth luminal borders, in contrast to the pseudo-papillae of tumor cell necrosis that is common in metastatic TCC (10,17). Another study has shown that the morphological similarity between transitional cell carcinoma of the ovary and its counterpart from the urinary bladder does not indicate any histogenic similarity, but CK7 and CK20, together with uroplakin III and WT1 may prove useful in distinguishing primitive TCCs of the ovary, and metastases from invasive TCC of the bladder to the ovary, the former being a variant morphology in the spectrum of surface epithelial carcinomas (11,18).…”
Section: Metastatic Tcc To the Ovariesmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a component of benign or borderline Brenner tumor confirms an ovarian primary tumor. TCC of the ovaries has mucin pools and thick papillae with smooth luminal borders, in contrast to the pseudo-papillae of tumor cell necrosis that is common in metastatic TCC (10,17). Another study has shown that the morphological similarity between transitional cell carcinoma of the ovary and its counterpart from the urinary bladder does not indicate any histogenic similarity, but CK7 and CK20, together with uroplakin III and WT1 may prove useful in distinguishing primitive TCCs of the ovary, and metastases from invasive TCC of the bladder to the ovary, the former being a variant morphology in the spectrum of surface epithelial carcinomas (11,18).…”
Section: Metastatic Tcc To the Ovariesmentioning
confidence: 99%
“…Primary TCC accounts for 1-2% of all ovarian tumors (10,17). TCC of the ovary is a recently recognized subtype of ovarian surface epithelial-stromal cancer, and studies of its morphology are rare.…”
Section: Metastatic Tcc To the Ovariesmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Advanced-stage bladder cancer presents with transmural involvement of the bladder wall and may show regional extensions into adjacent organs, including the colon, prostate, uterus, vaginal wall, and occasionally, adnexal structures. [13][14][15] By contrast, serous carcinoma arising in the gynecologic tract typically shows a complex adnexal and/or uterine mass that may be associated with pelvic carcinomatosis and regional implants, including to the bladder peritoneal surface. 12, 16,17 Given those unique presentations, the clinical impression derived from imaging, serum and urine analyses, and clinical examination readily distinguishes those 2 entities in most patients, which in turn, informs histopathologic diagnosis if tissue analysis is undertaken before surgical intervention.…”
Section: Analysis Of An Immunohistochemical Panel For Ck7 Wt1 Upiimentioning
confidence: 99%
“…However, significant diagnostic conundrums associated with areas of clinicopathologic overlap between those entities may occasionally occur. 7,15,18,19 We identified 5 patients whose clinical presentation resulted in a differential diagnosis of bladder carcinoma. Review of those and additional cases identified a spectrum of clinical, morphologic, and immunohistochemical features that could lead to an erroneous diagnosis and improper patient treatment.…”
Section: Analysis Of An Immunohistochemical Panel For Ck7 Wt1 Upiimentioning
confidence: 99%